The Performative Power of Vocality - MAGNAT, VIRGINIE (Routledge Voice Studies, 2020)
The Performative Power of Vocality offers a fresh perspective on voice as a subject of critical inquiry by employing an interdisciplinary and cross-cultural approach. Conventional treatment of voice in theatre and performance studies too often regards it as a subcategory of actor training, associated with the established methods that have shaped voice pedagogy within Western theatre schools, conservatories, and universities. This monograph significantly deviates from these dominant models through its investigation of the non-discursive, material, and affective efficacy of vocality, with a focus on orally transmitted vocal traditions. Drawing from her performance training, research collaborations, and commitment to cultural diversity, Magnat proposes a dialogical approach to vocality. Inclusive of established, current, and emerging research perspectives, this approach sheds light on the role of vocality as a vital source of embodied knowledge, creativity, and well-being grounded in process, practice, and place, as well as a form of social and political agency. An excellent resource for qualitative researchers, artist-scholars, and activists committed to decolonization, cultural revitalization, and social justice, this bookopens up new avenues of understanding across Indigenous and Western philosophy, performance studies, musicology, ethnomusicology, sound and voice studies, anthropology, sociology, phenomenology, cognitive science, physics, ecology, and biomedicine. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.